Increasing Entrepreneurship during Covid-19 Pandemic Time Economic Crisis - Rananda Septanta; Adi Sofyana Latif; Chaeru Syahru Ramdani; Rijal Arslan; Yunus Nurhasan (CV. Creative Tugu Pena, 2022)
The article of community service was to provide assistance about the innovation of entrepreneurial business products during the pandemic Covid-19, especially at Pamulang area. The method used Asset Based Community (ABCD) that utilize the potential asset of community; individual, social and infrastructure. The facilitator together with multi-stakeholders and assisted parties conducts seminars on innovation in entrepreneurship which included financial planning, and the application of business ethics. The facilitator also carried out a psychological test which was done by distributing questions to the participants with the aim of knowing the characteristics and behavior of participants in doing business. The participant was 50 participants of the local community at Pamulang orphans and poor people as well as Pamulang University students who also attended and followed all materials and discussions that occur during the event. Hence, the business goal was achieved, namely maximizing existing profits through selling the products. Keywords: Economic Crisis Covid-19, Entrepreneurship Economic, Economic Crisis